Ether-based polymer solid electrolyte lithium battery constructed by synergy of sulfolane and SbF3 and preparation method of ether-based polymer solid electrolyte lithium battery
By constructing the solid electrolytes in lithium batteries to construct ether -based polymers, the in situ aggregation process is used to form a close contact with the electrode and electrolyte, which solves the problem of liquid electrolyte leakage and the unstable electrode/electrolyte interface. Ion conductivity, mechanical strength, and thermal stability have improved the safety and cycle stability of the battery.
Patent Information
- Application Number
- CN202411447594.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
The flash point of liquid electrolyte in existing lithium batteries is low, easy to leak, lead to combustion and explosion, and the electrode/electrolyte interface is unstable, which is easy to produce lithium dendrites, affecting battery performance and safety.
The cycloid -chore coordinates SBF3 to build a solid electrolyte of ether -based polymer, and a tight electrode and electrolyte contact in the battery through the in -situ aggregation process to reduce the interface side -by -side reaction, and optimize the front -drive body solution formula to improve the electrolyte ion conductivity and mechanical strength.
The high ion conductivity, mechanical strength and thermal stability of lithium batteries are realized, the production of lithium branches crystals is suppressed, the safety and cycle stability of the battery are improved, and the production efficiency is improved and the cost is reduced.
Smart Images

Figure CN119340467A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to an ether-based polymer solid electrolyte lithium battery constructed by sulfolane and SbF3, and a preparation method thereof. Background Art
[0002] In the past few decades, lithium-ion batteries have miraculously dominated the field of electrochemical energy storage. With its advantages of no memory effect, low self-discharge rate, long cycle life, and low environmental pollution, lithium batteries have been widely used in mobile phones, computers, drones, aerospace, and new energy vehicles. However, the development of lithium batteries is still facing huge challenges. On the one hand, the flash point of liquid electrolyte solvents is low and easy to leak, which leads to combustion and explosion. The comprehensive performance of the electrolyte needs to be improved. On the other hand, the electrode / electrolyte interface is unstable, which easily produces lithium dendrites, triggering side reactions and continuously deteriorating battery performance. When the dendrites pierce the diaphragm, they will also cause short circuits and cause safety problems. Especially when matched with high-voltage ternary cathodes, higher requirements are placed on the oxidation stability and safety of electrolysis. Designing and developing new solid electrolyte materials is an effective solution strategy.
[0003] However, the research and development and industrial development of solid-state batteries still face some difficulties and challenges. For example, the interface in solid-state batteries has both physical contact and chemical contact, and the electrolyte and electrode materials of solid-state batteries are solid, which lack fluidity compared to liquid materials, and the degree of contact surface wetting is also low. It is difficult for solid electrolytes and solid electrodes to maintain intact interfacial contact, which will lead to increased contact resistance and heat during charging and discharging, affecting the overall performance of the battery. It is still challenging to retain the many excellent properties of traditional liquid electrolytes in an all-solid-state system. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a solid polymer electrolyte having good interface contact, high ionic conductivity, good mechanical strength, good thermal stability, and good compatibility with a graphite negative electrode, and provides a solid polymer electrolyte lithium battery with higher energy density.
[0005] The present invention adopts the following technical solution:
[0006] A method for preparing a lithium battery with an ether-based polymer solid electrolyte constructed by sulfolane and SbF3, wherein a poly-1,3-dioxolane (PDOL)-based solid polymer electrolyte with an appropriate amount of sulfolane (SL) as a co-solvent is constructed by in-situ polymerization, comprising the following steps:
[0007] S1. Evenly dispersing lithium salt in a 1,3-dioxolane (DOL)-based solvent, adding additives, and mixing evenly to obtain a precursor solution;
[0008] S2. Assemble the battery according to the assembly method of the liquid lithium battery, assemble the battery in the order of the negative electrode shell, the spring, the gasket, the negative electrode, the diaphragm, the positive electrode and the positive electrode shell, inject the precursor solution as the electrolyte, and then compact it through the sealing machine. After the assembly, let it stand for 24 hours until the electrode is completely wetted, wherein the assembly method of the liquid lithium battery is the prior art;
[0009] S3, after standing still, heating is performed, and the added lithium salt and additives induce polymerization of 1,3-dioxolane (DOL) to form a polymerized solid electrolyte, thereby obtaining a solid electrolyte lithium battery.
[0010] In the step S1, the molar volume ratio of the lithium salt, the solvent and the additive is 1.2 mol:1 L:(0.1-0.5 mmol).
[0011] The solvents of the precursor solution in step S1 are 1,3-dioxolane (DOL) and sulfolane (SL), wherein the volume ratio of sulfolane is 5-50%.
[0012] The lithium salt of the precursor solution in step S1 is at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
[0013] The total solubility of the lithium salt in the precursor solution is: 1.2 mol / L.
[0014] The additive of the precursor solution in step S1 is a trace amount of SbF3, and its solubility is 0.1-0.5mmol / L.
[0015] The standing time in step S3 is 1-24h.
[0016] In step S3, the heating temperature is 45-60° C. and the heating time is 2-24 hours.
[0017] An ether-based polymer solid electrolyte lithium battery obtained according to the above preparation method.
[0018] The technical solution of the present invention has the following advantages:
[0019] A. The present invention achieves close contact between the electrode and the electrolyte through an in-situ polymerization process, reduces interfacial side reactions, effectively inhibits the generation of lithium dendrites, and improves the safety and cycle stability of the battery.
[0020] B. Cyclopentane, as a polar aprotic solvent, participates in the solvation of lithium salts and significantly promotes the kinetics of ion migration, so that the solid polymer electrolyte prepared by the present invention has higher ion conductivity and lithium ion migration number, thereby improving the charge and discharge performance of the battery.
[0021] C. By optimizing the formula design of the precursor solution and the skeleton material, the solid polymer electrolyte prepared in the present invention not only has good ionic conductivity, but also has excellent mechanical strength and thermal stability, meeting the use requirements of the battery under harsh conditions such as high strength and high temperature.
[0022] D. The in-situ polymerization process of the present invention is compatible with the existing battery process system, and realizes the simultaneous manufacture of solid electrolytes and assembly of batteries, thereby improving production efficiency, reducing costs, and providing strong support for the large-scale application of solid-state batteries.
[0023] E. The solid polymer electrolyte provided by the present invention has good compatibility with the graphite negative electrode, so that the battery can be matched with positive and negative electrode materials with higher energy density, thereby improving the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a polymerization mechanism diagram of a DOL-based gel electrolyte according to Example 3 of the present invention;
[0026] Figure 2 This is a schematic diagram of the electrode-electrolyte cross section of the LiFePO4 battery in Example 3 of the present invention;
[0027] Figure 3 This is an EIS fitting curve diagram of Example 3 containing different amounts of SbF3 added in the present invention applied to LiFePO4 batteries;
[0028] Figure 4 This is the cycle performance diagram of Example 3 at 0.5C;
[0029] Figure 5 This is a diagram of the direct combustion test of the solid electrolyte in Example 3. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0033] S1. Dissolve 0.5mmol SbF3 and 0.2mol LiPF6 in 0.2L SL, and dissolve 1mol LiTFSI in 0.8L DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiPF6+0.5mM SbF3 in DOL:SL, where the volume ratio of SL is 20%;
[0034] S2, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0035] S3. After assembling the battery, let it stand for 2 hours, and then heat it at 60°C for 12 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0036] Example 2
[0037] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0038] S1. Dissolve 0.5mmol SbF3 and 0.2mol LiPF6 in 0.2L SL, and dissolve 1mol LiTFSI in 0.8L DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiPF6+0.5mM SbF3 in DOL:SL, where the volume ratio of SL is 20%;
[0039] S2, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0040] S3. After assembling the battery, let it stand for 10 hours, and then heat it at 45°C for 2 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0041] Example 3
[0042] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0043] S1. Dissolve 0.5mmol of SbF3 and 0.5mol of LiDFOB in 0.2L of SL, and dissolve 0.7mol of LiTFSI in 0.8L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 0.7MLiTFSI+0.5M LiDFOB+0.5mM SbF3 in DOL:SL, and the volume ratio of SL is 20%.
[0044] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0045] S3. After assembling the battery, let it stand for 2 hours, and then heat it at 60°C for 12 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0046] Example 4
[0047] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0048] S1. Dissolve 0.5mmol of SbF3 and 0.2mol of LiDFOB in 0.1L of SL, and dissolve 1mol of LiTFSI in 0.9L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiDFOB+0.5mM SbF3 in DOL:SL, and the volume ratio of SL is 10%.
[0049] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0050] S3. After assembling the battery, let it stand for 2 hours, and then heat it at 60°C for 12 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0051] Example 5
[0052] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0053] S1. Dissolve 0.2mmol of SbF3 and 0.2mol of LiDFOB in 0.3L of SL, and dissolve 1mol of LiTFSI in 0.7L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2MLiDFOB+0.2mM SbF3 in DOL:SL, and the volume ratio of SL is 30%.
[0054] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0055] S3. After assembling the battery, let it stand for 6 hours, and then heat it at 50°C for 12 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0056] Example 6
[0057] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0058] S1. Dissolve 0.5mmol of SbF3 and 0.2mol of LiDFOB in 0.5L of SL, and dissolve 1mol of LiTFSI in 0.5L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiDFOB+0.5mM SbF3 in DOL:SL, and the volume ratio of SL is 50%.
[0059] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0060] S3. After assembling the battery, let it stand for 8 hours, and then heat it at 45°C for 2 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0061] Example 7
[0062] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0063] S1. Dissolve 0.5mmol of SbF3 and 0.5mol of LiDFOB in 0.2L of SL, and dissolve 0.7mol of LiTFSI in 0.8L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 0.7MLiTFSI+0.5MLiDFOB+0.5mM SbF3 in DOL:SL, and the volume ratio of SL is 20%.
[0064] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0065] S3. After assembling the battery, let it stand for 2 hours, and then heat it at 60°C for 6 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0066] Example 8
[0067] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0068] S1. Dissolve 0.5 mmol of SbF3 in 0.2 L of SL and 1.2 mol of LiTFSI in 0.8 L of DOL. After the two solutions are completely dissolved, mix them to make the composition of the mixed solution: 1.2 M LiTFSI + 0.5 mM SbF3 in DOL: SL, and the volume ratio of SL is 20%.
[0069] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0070] S3. After assembling the battery, let it stand for 12 hours, and then heat it at 60°C for 10 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0071] Example 9
[0072] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0073] S1. Dissolve 0.3 mmol of SbF3 and 1.2 mol of LiDFOB in 0.05 L of SL. After complete dissolution, mix the above solution with 0.95 L of DOL solution to make the composition of the mixed solution: 1.2 M LiDFOB + 0.3 mM SbF3 in DOL: SL, and the volume ratio of SL is 5%.
[0074] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0075] S3. After assembling the battery, let it stand for 16 hours, and then heat it at 60°C for 12 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0076] Example 10
[0077] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0078] S1. Dissolve 0.4 mmol of SbF3 and 0.6 mol of LiDFOB in 0.2 L of SL, and dissolve 0.8 mol of LiTFSI in 0.8 L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 0.8 M LiTFSI + 0.6 M LiDFOB + 0.4 mM SbF3 in DOL: SL, the volume ratio of SL is 20%, and an ether-based polymer solid electrolyte lithium battery is obtained.
[0079] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0080] S3. After assembling the battery, let it stand for 2 hours, and then heat it at 60°C for 16 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0081] Embodiment 11
[0082] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0083] S1. Dissolve 0.1mmol of SbF3 and 0.2mol of LiDFOB in 0.2L of SL, and dissolve 1mol of LiTFSI in 0.8L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiDFOB+0.1mM SbF3 in DOL:SL, and the volume ratio of SL is 20%.
[0084] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0085] S3. After assembling the battery, let it stand for 2 hours, and then heat it at 60°C for 12 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0086] Example 12
[0087] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0088] S1. Dissolve 0.1mmol of SbF3 and 0.2mol of LiDFOB in 0.2L of SL, and dissolve 1mol of LiTFSI in 0.8L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiDFOB+1mM SbF3 in DOL:SL, and the volume ratio of SL is 20%.
[0089] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0090] S3. After assembling the battery, let it stand for 2 hours, and then heat it at 50°C for 12 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0091] Embodiment 13
[0092] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0093] S1. Dissolve 0.1mmol of SbF3 and 0.2mol of LiDFOB in 0.4L of SL, and dissolve 1mol of LiTFSI in 0.6L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiDFOB+0.1mM SbF3 in DOL:SL, and the volume ratio of SL is 40%.
[0094] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0095] S3. After assembling the battery, let it stand for 1 hour, and then heat it at 55°C for 24 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0096] Embodiment 14
[0097] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0098] S1. Dissolve 0.1mmol of SbF3 and 0.2mol of LiDFOB in 0.2L of SL, and dissolve 1mol of LiTFSI in 0.8L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiDFOB+0.1mM SbF3 in DOL:SL, and the volume ratio of SL is 20%.
[0099] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0100] S3. After assembling the battery, let it stand for 12 hours, and then heat it at 60° C. for 12 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0101] Embodiment 15
[0102] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0103] S1. Dissolve 0.1mmol of SbF3 and 0.2mol of LiDFOB in 0.2L of SL, and dissolve 1mol of LiTFSI in 0.8L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiDFOB+0.1mM SbF3 in DOL:SL, and the volume ratio of SL is 20%.
[0104] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0105] S3. After assembling the battery, let it stand for 4 hours, and then heat it at 45°C for 12 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0106] Example 16
[0107] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0108] S1. Dissolve 0.3mmol of SbF3 and 0.2mol of LiDFOB in 0.2L of SL, and dissolve 1mol of LiTFSI in 0.8L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiDFOB+0.3mM SbF3 in DOL:SL, and the volume ratio of SL is 20%.
[0109] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0110] S3. After assembling the battery, let it stand for 24 hours, and then heat it at 60°C for 24 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0111] Embodiment 17
[0112] This embodiment provides a method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, comprising the following steps:
[0113] S1. Dissolve 0.1mmol of SbF3 and 0.2mol of LiDFOB in 0.2L of SL, and dissolve 1mol of LiTFSI in 0.8L of DOL. After they are completely dissolved, mix the two solutions to make the composition of the mixed solution: 1M LiTFSI+0.2M LiDFOB+0.1mM SbF3 in DOL:SL, and the volume ratio of SL is 20%.
[0114] S2. Inject the mixed solution into the button battery. The whole process is completed in an inert gas.
[0115] S3. After assembling the battery, let it stand for 2 hours, and then heat it at 60°C for 2 hours to obtain an ether-based polymer solid electrolyte lithium battery.
[0116] The accompanying drawings take Example 3 as an example. Figure 1 This is a polymerization mechanism diagram of the DOL-based solid electrolyte of Example 3. After the initiator SbF3 is added to the precursor solution, the DOL ring-opening polymerization is initiated to form PDOL, and the electrolyte is transformed into a solid state.
[0117] Figure 2 It is a schematic diagram of the electrode-electrolyte cross-section of the LiFePO4 battery assembled in Example 3, showing the morphological characteristics of the close fit between the positive electrode, the separator and the negative electrode in the battery of the solid electrolyte formed by in-situ polymerization, reflecting the full infiltration of the electrolyte in the electrodes.
[0118] Figure 3 The EIS fitting curve of Example 3 containing different amounts of SbF3 added in the present invention applied to LiFePO4 batteries is shown in Figure 1. Due to the in-situ conversion of the Li3Sb-LiF interface, the resistance of the battery increases with the amount of SbF3, among which the generation of excessive LiF is the main reason for the increase in interface resistance. The change in resistance shows that a more uniform interface is generated when 0.5mM SbF3 is added.
[0119] Figure 4 Figure 2 shows the cycling performance of the LiFePO4||Gr battery at 0.5C using the traditional liquid electrolyte (LE) and Example 3. The solid electrolyte exhibited a cycling performance of 155.9 mAh g -1 The discharge capacity is much higher than that of traditional liquid electrolytes (144.2 mAh g -1 ). In subsequent cycle tests, the conventional liquid electrolyte showed a capacity retention rate of 74.4% within 300 cycles, as the conventional liquid electrolyte could not produce a stable interface on lithium metal and continued to decompose. In contrast, the solid electrolyte can maintain 96.1% of the capacity after 300 cycles, thanks to the chemical and electrochemical stability of the positive electrode components and the construction of the unique alloy hybrid interface of the negative electrode.
[0120] Figure 5 The solid electrolyte of Example 3 was directly subjected to a combustion test. The results showed that the solid electrolyte of Example 3 exhibited a high degree of non-flammability.
[0121] As a polar aprotic solvent, sulfolane participates in the solvation of lithium salts and significantly promotes the kinetics of ion migration, resulting in higher ionic conductivity and lithium ion migration number (t Li + ).
[0122] In-situ polymerization is a method in which liquid monomers, lithium salts, polymer initiators and other components of the electrolyte system are uniformly mixed in advance and then injected into the battery to undergo a polymerization reaction from liquid to solid phase. It is favored due to its good compatibility with electrodes and its similar process to traditional liquid electrolyte systems. Compared with the traditional solution casting method, the solid polymer electrolyte obtained by the in-situ polymerization process has a closer contact with the electrode, making the Li + The distribution is uniform and the concentration gradient is reduced, thereby inhibiting the interfacial side reactions and the formation of lithium dendrites.
[0123] In the present invention, the assembly method of liquid lithium battery (such as button battery) is a prior art.
[0124] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3, characterized in that: The steps include: S1. Evenly dispersing lithium salt in a 1,3-dioxolane (DOL)-based solvent, adding additives, and mixing evenly to obtain a precursor solution; S2. Assemble the battery according to the assembly method of the liquid lithium battery, assemble the battery in the order of the negative electrode shell, the spring, the gasket, the negative electrode, the diaphragm, the positive electrode and the positive electrode shell, inject the precursor solution as the electrolyte, and then compact it through the sealing machine. After assembly, let it stand for 24 hours until the electrode is completely wetted; S3, after standing still, heating is performed, and the added lithium salt and additives induce polymerization of 1,3-dioxolane (DOL) to form a polymerized solid electrolyte, thereby obtaining a solid electrolyte lithium battery.
2. The method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3 according to claim 1, characterized in that: In the step S1, the molar volume ratio of the lithium salt, the solvent and the additive is 1.2 mol:1 L:(0.1-0.5 mmol).
3. The method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3 according to claim 1, characterized in that: The solvents of the precursor solution in step S1 are 1,3-dioxolane (DOL) and sulfolane (SL), wherein the volume ratio of sulfolane is 5-50%.
4. The method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3 according to claim 1, characterized in that: The lithium salt of the precursor solution in step S1 is at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
5. The method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3 according to claim 4, characterized in that: The total solubility of the lithium salt in the precursor solution is: 1.2 mol / L.
6. The method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3 according to claim 1, characterized in that: The additive of the precursor solution in step S1 is a trace amount of SbF3, and its solubility is 0.1-0.5mmol / L.
7. The method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3 according to claim 1, characterized in that: The standing time in step S3 is 1-24h.
8. The method for preparing an ether-based polymer solid electrolyte lithium battery using sulfolane and SbF3 according to claim 1, characterized in that: In step S3, the heating temperature is 45-60° C. and the heating time is 2-24 hours.
9. An ether-based polymer solid electrolyte lithium battery obtained by the preparation method according to any one of claims 1 to 8.